APLIKASI “SIPELAPOR” UNTUK PENGOLAHAN NILAI RAPOR PADA SMP NEGERI 26 PURWOREJO - Eka Yulistia Nurwanti; Anastasia Meyliana (APMMI - Asosiasi Profesi Multimedia Indonwsia, 2019)
Abstract - The education process is inseparable from teaching and learning activities in the classroom. One of the tools that can be used to measure and evaluate the results of KBM is report card grades. At SMP Negeri 26 Purworejo report processing still requires a long time because the process is done manually. Therefore, the purpose of making the